PENGARUH KONSUMSI REBUSAN TELUR AYAM RAS TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI NAGARI SUNGAI RUMBAI TIMUR - Purwati, Rati; Mumtazah, Siti Ainawati; Wijayanti, Ria Lestari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Perineal wounds are tears that occur during childbirth, either spontaneously or with the use of instruments or procedures. Proper care of perineal tissue wounds is essential to prevent infection. Protein intake greatly influences the healing process of perineal wounds. The nutritional content of eggs includes more than 90% calcium and iron; one egg contains 6 grams of high-quality protein and 9 essential amino acids. High-protein foods can be obtained from chicken eggs, which contain 12.58 grams of protein. Poor wound care can lead to complications such as urinary tract infections or genital tract infections. The purpose of this study was to determine whether boiled chicken egg consumption has an effect on perineal wound healing in postpartum mothers. This study used a true experimental design with a two-group posttest-only method. The population consisted of 47, with a total sample of 20 postpartum mothers with second-degree perineal wounds, selected through purposive sampling. The study was conducted over 7 days. Data analysis used the Mann-Whitney U Test because the data distribution was not normal. The results showed a p-value = 0.002 (p < 0.05), indicating a significant difference in perineal wound healing time between the intervention and control groups. The effectiveness of chicken eggs, which contain high-quality protein and essential amino acids, can accelerate tissue repair within 7 days. In conclusion, the frequency distribution of perineal wound healing after consuming boiled eggs shows an accelerated healing process, with wounds drying faster, stitches closing more quickly, and pain decreasing compared to the group that did not consume boiled eggs.Keywords: Perineal Wounds, Postpartum, Protein, Chicken Eggs